Analisis Biologi Terapan Berbasis Variabel Lingkungan dan Molekuler - Melati Permata; Bayu Rahman (Lembaga Publikasi Ilmiah Nusantara, 2026)
The advancement of applied biology based on molecular approaches has significantly improved the accuracy of environmental analysis. This study aims to examine the relationship between environmental variables and molecular responses of organisms as indicators of ecosystem change. The research applies an integrative approach using environmental DNA (eDNA), environmental RNA (eRNA), molecular biomarkers, and mass spectrometry techniques for environmental monitoring. Data were compiled from recent empirical studies demonstrating that eDNA-based methods achieve species-level detection accuracy exceeding 90%. In addition, molecular biomarkers enable the identification of pollutant exposure at the sub-cellular level prior to observable ecological impacts. The results indicate that environmental variables such as temperature, pH, and pollutant concentration show strong correlations with gene expression and microbial community dynamics. The integration of molecular and environmental data produces more accurate predictive models for detecting ecosystem degradation. This study confirms that molecular biology approaches play a critical role in developing precise, rapid, and sustainable biomonitoring systems for environmental management.